2011
DOI: 10.1007/s10974-011-9267-4
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain mRNA isoforms are expressed in two distinct cohorts during C2C12 myogenesis

Abstract: The regulation of muscle fibre transitions has mainly been studied in vivo using conventional histological or immunohistochemical techniques. In order to investigate the molecular regulation of myosin heavy chain (MyHC) isoform expression in cell culture studies, we first characterised the normal transitions in endogenous expression of the MyHC isoforms and the myogenic regulatory factors during differentiation of C2C12 muscle cells. Interestingly, across the time course of differentiation, MyHC mRNA isoforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
95
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 32 publications
18
95
1
Order By: Relevance
“…C2C12 cells formed visible myotubes after 4 days (Figure 2A), with differentiation confirmed by measuring various myosin heavy chain ( Myh7, 4, 2, 1 ) mRNA levels, known markers of muscle cell differentiation (Brown et al, 2012). All Myh mRNAs were elevated by day 3 ( p < 0.01) and day 4 ( p < 0.001) when compared to day 0 (Figure 2B).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…C2C12 cells formed visible myotubes after 4 days (Figure 2A), with differentiation confirmed by measuring various myosin heavy chain ( Myh7, 4, 2, 1 ) mRNA levels, known markers of muscle cell differentiation (Brown et al, 2012). All Myh mRNAs were elevated by day 3 ( p < 0.01) and day 4 ( p < 0.001) when compared to day 0 (Figure 2B).…”
Section: Resultsmentioning
confidence: 77%
“…They also did not clearly describe if proliferation was measured in the presence or absence of serum, nor was the level of cell confluence at the time of treatment with G-CSF stated (Hara et al, 2011), making their results difficult to interpret. Myosin heavy chain proteins regulate skeletal muscle contraction and their mRNA levels are significantly increased during myogenesis (Brown et al, 2012). In the current study mRNA expression levels for myosin heavy chains ( Myh -7, - 4 , - 2 and - 1 ) continued to increase throughout differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation process is associated with the expression of differentiation markers such as myosin heavy chain (MHC), which is considered a typical marker for terminally differentiated muscle cells [14]. Glucose starvation is known to impair the differentiation process [15], [16], therefore we investigated whether galactose can be substituted for glucose.…”
Section: Resultsmentioning
confidence: 99%
“…The expression level of MyoD in JAZF1-OE or JAZF1-DR cells was very similar to that in each control cells. These results indicated that JAZF1 expression preferentially affected the myogenic genes expressed later during myogenic differentiation and in adult skeletal muscle, such as Mrf4, Mef2c, Myh1, and Ckm [18][19][20][21][22].…”
Section: Their Myogenic Differentiationmentioning
confidence: 86%